Characteristics, Clinical, and Trichoscopic Features in Pediatric Patients with Alopecia Areata: A Single-Center Observational Study at the Dermatology Clinic of Dr. M. Djamil General Hospital Padang - Yenny, Satya Wydya; Yola Fadilla; Raja Eka Citra Kalisa (HM Publisher, 2024)
Background: Alopecia areata (AA) is an autoimmune disease that causes patchy hair loss. In children, AA can have a significant psychological impact. This study aims to identify the characteristics, clinical and trichoscopic features of AA pediatric patients at the dermatology clinic of Dr. M. Djamil General Hospital Padang. Methods: This cross-sectional analytical observational study involved pediatric patients (<18 years) with a diagnosis of AA who came to the dermatology clinic of Dr. M. Djamil General Hospital Padang between January 2020 to December 2023. Demographic data, disease history, clinical features, and trichoscopy examination results were collected and analyzed descriptively. Results: A total of 125 pediatric AA patients met the inclusion criteria. The majority of patients were female (62.4%) with a mean age of 10.5 years. The most common form of AA is patchy (80%), followed by alopecia totalis/universalis (12%) and ophiasis (8%). A history of atopy was found in 35.2% of patients. The most frequently found trichoscopic features were yellow dots (78.4%), black dots (64%), and broken hairs (56%). Conclusion: This study provides a comprehensive description of the characteristics, clinical and trichoscopic characteristics of AA pediatric patients at Dr. M. Djamil General Hospital Padang. These findings may provide a basis for the development of better management strategies for AA in children.